2021
DOI: 10.1016/j.esmoop.2021.100299
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of the HER2 status of circulating tumor cells in metastatic breast cancer patients screened for participation in the DETECT study program

Abstract: Background: Circulating tumor cells (CTCs) have been reported to predict clinical outcome in metastatic breast cancer (MBC). Biology of CTCs may differ from that of the primary tumor and HER2-positive CTCs are found in some patients with HER2-negative tumors. Patients and methods: Patients with HER2-negative MBC were screened for participation in DETECT III and IV trials before the initiation of a new line of therapy. Blood samples were analyzed using CELLSEARCH. CTCs were labeled with an anti-HER2 antibody an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…With our test, we show sensitivity of 83%, 80% and 63% and specificity of 89%, 94%, 89% for ER, PR, HER2 respectively on CTCs derived from known cancer patients. Studies have reported significant heterogeneity between ER/PR/HER2 protein expression in CTCs and primary tumor/metastatic biopsy, and this status may change over time due to therapy [11,[42][43][44][45]. In our CTC-based test, we observed slightly lower sensitivity for HER2 by ICC than other markers.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…With our test, we show sensitivity of 83%, 80% and 63% and specificity of 89%, 94%, 89% for ER, PR, HER2 respectively on CTCs derived from known cancer patients. Studies have reported significant heterogeneity between ER/PR/HER2 protein expression in CTCs and primary tumor/metastatic biopsy, and this status may change over time due to therapy [11,[42][43][44][45]. In our CTC-based test, we observed slightly lower sensitivity for HER2 by ICC than other markers.…”
Section: Discussionmentioning
confidence: 50%
“…ER, PR and HER2 status is prognostic and predictive in breast cancer [41,42]. The choice of targeted therapies in breast, ovarian and uterine neoplasms depends on the expression of ER/PR on the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, in patients with HER2-negative metastatic breast cancer screened for participation in the DETECT study and analyzed using the CellSearch system, the presence of ≥1 CTC with strong HER2 staining was associated with a shorter OS. A possible explanation for this contrasting finding is that patients receiving HER2-directed treatment based on the detection of HER2-positive CTC were not included in the survival analysis [19]. In our study with a pragmatic approach, 38% of patients were receiving HER2-targeted therapy, which might have altered the clinical course of disease and improved the outcome for patients.…”
Section: Discussionmentioning
confidence: 84%
“…Between November 2016 and February 2018, 39 women were accrued. Patients underwent SRT with radiosurgery (SRS) or stereotactic fractionated radiotherapy (SFRT) in 68% (27) and 31% (12) of cases, respectively, with a median prescribed dose of 20 Gy (15)(16)(17)(18)(19)(20)(21)(22) with SRS and 27.5 Gy (25-30) in five fractions with SFRT.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The CTC clearance at the end of treatment was not associated with OS, although better OS was observed in patients with no evidence of CTCs at first follow-up compared to patients with detectable CTCs (HR 0.36; 95% CI, 0.17-0.76; p = 0.005) (Table 1). Finally, in a very recent research article also within the DETECT program, the authors analysed the HER2 status of CTCs in patients HER2-negative tumours and its clinical significance [54]. Herein, CTCs HER2 status was analysed in 1159 CTCs-positive patients.…”
Section: Circulating Tumour Cells In Her2-positive Metastatic Breast ...mentioning
confidence: 99%